(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Asadi, Dewi N, Nugroho K, Terryana RT, Mastur, Lestari P. 2020. Evaluation of SSR and important agronomical characters of promising mutant lines of soybean. Biodiversitas 21: 299-310. Improved soybean (Glycine max (L.) Merr.) varieties resistant to major pest or disease, and in accordance with consumer preferences are important in breeding programs to raise their productivity. Identification of superior promising mutant lines of soybean before releasing them needs multiple environment trials complemented with molecular assay. This study aimed to assess morpho-agronomical and molecular characters using SSR markers of promising mutant lines of soybean (Glycine max (L.) Merr.). A total of 14 SSR markers were used to evaluate 20 mutant lines along with their parental lines and check varieties, and eight different locations were chosen to field evaluation of 11 selected lines induced by gamma-ray. Values of Polymorphism Information Content, allele number, and gene diversity index were high, indicating the great genetic diversity among these mutant lines, and far distant from their parental lines. Phylogenetic tree also supported the distinguishable among gamma ray-induced mutant lines compared to the parental lines. The significant interaction between promising line and environment showed their high adaptability and stable yield in various environments. Biosoy-8 (2.713 ton/ha) and Biosoy-11 (2.631 ton/ha) revealing the high yields lines supported with the molecular information could be potential to be released as new varieties and can direct their efficient utilization for field application or further improvement scheme.